THE EFFECT OF LEARNING ACHIEVEMENT AND WORK MOTIVATION ON WORK READINESS WITHINTERNSHIP EXPERIENCE AS A MEDIATION FOR FINAL-YEAR STUDENTS OF THE MANAGEMENT STUDY PROGRAM, CLASS 2021 MALIKUSSALEH UNIVERSITY - Alvia Fitriana; Yusniar; Faisal Matriadi; Khairawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of academic achievement and work motivation on job readiness, and to examine the role of internship experience as a mediating variable among final-year students of the Management Study Program, Malikussaleh University, intake of 2021. This study used primary data collected through questionnaires distributed to 118 respondents using a purposive sampling method. The data analysis technique used was SEM-PLS with the assistance of SmartPLS software version 4.0. Data validity was tested using convergent validity, discriminant validity, and average variance extracted (AVE), as well as model reliability, model fit, coefficient of determination (R²), Q-square, and effect size. The results showed that academic achievement significantly influenced job readiness, as did work motivation, which also had a significant influence on job readiness. Internship experience was proven to act as a mediating variable between academic achievement and job readiness, as well as between work motivation and job readiness. This indicates that internship experience can strengthen the relationship between academic achievement and work motivation on student job readiness.Final Year of Management Study Program, Class of 2021, Malikussaleh University.